Pengaruh Kinerja Keuangan Perusahaan terhadap Pertumbuhan Laba pada Perusahaan Sektor Properti dan Real Estate - Ahyana, Vidya; Tiya Nurfauziah; Nella Yantiana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to test and evaluate the impact of the company's financial performance, which is determined by the ratio of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), on profit growth in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. The associative method is combined with the quantitative approach in this study. In addition, data analysis was carried out on a sample of 80 selected companies using the purposive sampling method, which was then outlier to eliminate extreme data using a boxplot in SPSS software. Multiple linear regression is used to analyze secondary data, i.e. the financial statements of the company. Classical assumption and hypothesis testing is used to support the results. The results of the analysis showed that the ROA variable of the tcount value < ttable (-0.598 < 1.66940) with a significance value of 0.552 > 0.05. The ROE variable of the tcount value < ttable (1.624 < 1.66940) with a significance value of 0.109 > 0.05. The NPM variable of the tcount value < ttable (0.229 < 1.66940) with a significance value of 0.820 > 0.05. Meanwhile, in the F test, the significance level was 0.039 < 0.05 and the Fcount value < Ftable (2.954 < 3.14). This means that partially or simultaneously the three variables have a positive influence on the company's profit growth. This study indicates that businesses in the property and real estate sector must improve asset utilization and cost management efficiency to increase profits. The results of this research can be a reference for investors and stakeholders in making more strategic investment decisions.